Risk Factors and Level of Listeria monocytogenes Contamination of Raw Pork in Retail Markets in China - Li, Hua; Wang, Pengfei; Lan, Ruiting; Luo, Lijuan; Cao, Xiaolong; Wang, Yi; Wang, Yan; Li, Hui; Zhang, Lu; Ji, Shunshi; Ye, Changyun (Frontiers in Microbiology, 2018)
Listeria monocytogenes can contaminate various foods via food processing environments and contamination of raw materials. There is a limited understanding of L. monocytogenes transmission in retail market and the role of insects in L. monocytogenes transmission in the retail environments. To better understand the risk factors of raw pork contamination, the prevalence of L. monocytogenes was examined in raw pork, retail environments and insects in a retail market over a six-month period from March to August in 2016 in Beijing, China. A total of 2,789 samples were collected, including 356 raw pork samples, 1,392 meat contact surface swabs (MCS), 712 nonmeat contact surface swabs (NMCS) and 329 insect samples. Overall, 424 (15.20%) of the samples were found to be contaminated by L. monocytogenes. Analyzed by serotyping, multilocus sequence typing and pulsed-field gel electrophoresis, the 424 L. monocytogenes isolates were divided into three serotypes (1/2c, 1/2a and 3a), 15 pulsotypes (PTs) and nine sequence types (STs), 1/2c/PT4/ST9 (244/424, 58%) was the most prevalent type of L. monocytogenes strains. The raw pork, MCS of the environments and insects were contaminated with higher levels of L. monocytogenes than NMCS of the environments, which suggested that cross contamination of L. monocytogenes between raw pork and the environment existed in the retail market, and long-term contaminated surfaces and vector insects would act as high risk factors to transmit L. monocytogenes to raw pork. Thus more effective strategies were needed to reduce the risk of retail pork meat contamination by L. monocytogenes and prevent foodborne human listeriosis.